DESIGN, MANUFACTURE AND TESTING OF A 3-AXIS LOAD CELL FOR GROUND REACTION FORCE MEASUREMENT ON FORCE PLATFORM - WICAKSANA SUWIRYA (NIM : 13106044); Tim Pembimbing : Dr. Ir. Andi Isra Mahyuddin; Dr. Ir. Tat, ALIT
In physics, a force is any influence that causes a free body to undergo a change in speed, direction, or shape. The importance of force causes the number of force measurement instruments are available. Load cell is a force measurement instrument that uses strain gage for converting the force into electrical signals. In biomechanics, kinetic parameters play important roles. One of the important parameters is the ground reaction force (GRF). There is a need to measure this force in the study of human motion. However, the available instruments are relatively expensive, so in order to develop an affordable force measurement system, in this project a load cell as a component of force platform was designed, manufactured, and tested. Several design alternatives were examined in order to obtain optimum load cell design capable of measuring GRF human movement in 3 axes simultaneously. The load cell has 3 segments which are designed to isolate 3-axis force. The test results showed that each load cell segment is sensitive only in one particular direction in accordance with design criteria. Comparison with simulation results found no significant difference in measured strain (14,49 % for vertical force ; 9.15%, for anterior-posterior force and 2.3% medial-lateral force).